Composición paisajista de la provincia de El Oro. - Cruz Vilela, Olinda Nelly (2015)
The province of El Oro for its geographical conformation is qualified by a number of geological story mesclados diversity of fauna and flora product of the variety of climate, give rise to a rich landscape view beauty and warmth, which permeates to all who may spectral and inspires artists and strangers. The perfect combination between nature and humans enables communication in different orders, as there is an open for inspiration, as orense field I feel motivated to move small `particles of these lush beauty in the" COMPOSITION LANDSCAPE OF THE PROVINCE OF GOLD “, theme I have taken the theme of the project prior to the titration of Fine Arts graduate research. The artists have the raw material to our fingertips to transcribe all those landscape, it is important to highlight the achievement of the information obtained through this enables documentation center the project and implement, using mixed media as Plastic printing mode.